The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ica.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of Ttz copper(II) complexes in the presence and absence of protons: Processes relevant to enzymatic nitrite reduction (TtzR,R′= tris(3-R, 5-R′-1, 2, 4-triazolyl)borate)

Abstract: Tris(triazolyl)borate (Ttz) is a proton responsive ligand, and the redox potential of Ttz complexes can be altered by protonation. Protonation events can therefore alter the thermodynamics of reduction of copper complexes, and this is relevant to nitrite reduction mediated by copper complexes wherein Cu(II) reduction to Cu(I) is the first step. The electrochemical behavior of tris(triazolyl)borate and the corresponding copper complexes, Ttz tBu,Me CuCl (1) and Ttz tBu,Me CuNO 2 (2), was investigated under both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…On account of the comparatively simple active site structure of CuNIR suggested by the crystallographic studies, a number of groups have developed simplified analogues of this enzyme based on tripodal N-donor ligands coordinated to a Cu center. , In many cases, these analogues also encapsulate the functionality of CuNIR (and so can mediate the reduction of nitrite to NO), normally with the use of stoichiometric sacrificial electron donors. There is also a distinct subset of such Cu–N donor complexes that can mediate the electrocatalytic reduction of nitrite to NO. In these latter cases in particular, the role of solution pH (or the presence of additional proton sources in nonaqueous media) has been shown to be critical, with acidic regimes being essential for catalytic reduction of nitrite to NO. This is perhaps not surprising, given the dependence of eq on the presence of protons.…”
Section: Introductionmentioning
confidence: 99%
“…On account of the comparatively simple active site structure of CuNIR suggested by the crystallographic studies, a number of groups have developed simplified analogues of this enzyme based on tripodal N-donor ligands coordinated to a Cu center. , In many cases, these analogues also encapsulate the functionality of CuNIR (and so can mediate the reduction of nitrite to NO), normally with the use of stoichiometric sacrificial electron donors. There is also a distinct subset of such Cu–N donor complexes that can mediate the electrocatalytic reduction of nitrite to NO. In these latter cases in particular, the role of solution pH (or the presence of additional proton sources in nonaqueous media) has been shown to be critical, with acidic regimes being essential for catalytic reduction of nitrite to NO. This is perhaps not surprising, given the dependence of eq on the presence of protons.…”
Section: Introductionmentioning
confidence: 99%
“…The different order trend found for the catalytic cycle implies that reduction from Cu II to Cu I may be a controlling factor during the catalytic cycle. Moreover, Papish 42 and Dilworth 45 both reported that the reduction of Cu II to Cu I should be a key step in enzymatic nitrite reductions. Therefore, we were further interested in the reduction behaviors of the three LCu II complexes and Cu II (NO 3 ) 2 •3H 2 O.…”
Section: Papermentioning
confidence: 99%
“…38 These Cu I -nitro and Cu II -nitrito complexes are good bioinspired compounds and allow chemists to understand each step of the nitrite reduction mechanism; however, the catalytic aspects of copper-mediated nitrite reductions are rare, although there are a number of studies on bioinspired electro-catalysts used for nitrite reduction. [39][40][41][42][43][44] Dilworth described catalytic studies on Cu II complexes that converted NO 2 − into NO (g) and N 2 O (g) by using L-ascorbic acid. 45 Inspired by the reactivities of known Cu I -nitro complexes, 26,27 we chose three typical ligands (neutral Me2 Tpm (L1), anionic Me2 Tp (L2), and neutral iPr TIC (L3; tris(1-methyl-2-isopropyl-4imidazolyl)-carbinol) to explore how the electron-donating ability of the ligand affects catalytic nitrite reduction from Cu II sources in comparison with stoichiometric nitrite reduction from Cu I -nitro species (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, bio-inspired CuNiRs are also studied using electrochemical methods in both organic ,, and aqueous solutions. ,, The first electrochemical studies on nitrite reduction were reported in 1993 and 1995 by the group of Komeda. , Herein, the authors report that [Cu(tmpa)(OH 2 )] 2+ (tmpa = tris(2-pyridylmethyl)amine, Cu(tmpa) , see Figure b) reduces NO 2 – electrocatalytically to NO. Later, the Meyerhoff group reported its use in NO-releasing catheters, showing that Cu(tmpa) is a stable catalyst for more than 7 days .…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of various Cu-(I) 20−30 and Cu(II) 22,26−29,31−41 model compounds with nitrite was investigated, and several Cu(II)−NO 27,42−44 and Cu(I)−NO 45−47 studies by Fujii and co-workers showed that a stepwise protonation mechanism is operative in dichloromethane, 23,25 and work by Hsu and co-workers sheds light on the possible formation of HNO 2 at low pH. 38 In recent years, bio-inspired CuNiRs are also studied using electrochemical methods in both organic 34,48,49 and aqueous solutions. 11−14,37,50−52 The first electrochemical studies on nitrite reduction were reported in 1993 and 1995 by the group of Komeda.…”
Section: ■ Introductionmentioning
confidence: 99%